Constructing a database for economic modelling from the System of National Accounts: a Social Accounting Matrix for Portugal - Santos, Susana (2009)
Based on the country's National Accounts, an aggregate Social Accounting Matrix (SAM) will be constructed for the Portuguese economy. The full consonance between the two will be demonstrated by identifying both the items and balances of the various internal accounts of the System of National Accounts in the constructed SAM. The balance of the government budget and the balance of payments will also be identified. Blocks of sub-matrices with common characteristics will be identified and described in terms of the national accounting transactions that are included in each of them. The SAM will be shown as a complete account of the circular flow in the economy and possible disaggregations will be explored in order to construct a database for economic modelling. From the Pilot-SAM for Portugal, the focus on households and employment will be specified in order to construct a database for a SAM-based CGE model with the aim of studying income distribution in Portugal.